Evaluation of the environment of the Shatt Al-Arab estuary and Iraqi marine waters using the Estuarine Biological Integrity Index (EBI) - Al-Shamary, Ahmed; younis, Kadhim (Iraqi Journal of Aquaculture, 2024)
A total of 9772 fish specimens were collected, including 91 species of bony fishes in the Shatt Al-Arab estuary and Iraqi marine waters, belonging to 72 genera and representing 48 families from January 2018 to December 2018 in three selected stations. The Estuarine Biological Integrity Index (EBI) was calculated in the current study through 13 units that included species richness units, fish community composition, and trophic guild units. The total Estuarine Biological Integrity Index (EBI) value reached 48.5, 55.9, and 57.4 for the three study stations. It was included in the impaired and marginally impaired evaluation in the different months within the study stations. The highest value of the index reached 71.42 in July at the Iraqi marine waters. It is evaluated as the marginally impaired category, and its lowest value was 41.47 in March at the Shatt Al-Arab estuary where it is assessed as the impaired category. The average total index value reached 55.61 and it is evaluated as in the impaired evaluation.